Investigating orthographic processing in Greek using eye tracking technology - Φελλά, Αργυρώ; Παπαδόπουλος, Τιμόθεος Κ. (Psychology: the Journal of the Hellenic Psychological Society, 2018)
The present study investigated the differences between children with reading difficulties (RD) and their controls (Grade 3 and Grade 6) on an orthographic processing task (OP), using eye-tracking technology. Grade 3 typically developing readers were used as reading age controls for the Grade 6 RD group. During the OP task, the participants had to identify the correct word in pairs of correctly spelled and phonologically correct but misspelled words. Two oculomotor movements, fixations and saccades, were recorded using an eye-tracking technology (EyeLink® 1000 Plus eye-tracker). The results revealed that Grade 6 RD group produced significantly longer fixations, shorter first fixations, and more saccades than their CA controls, suggesting a lack of established orthographic representations in their mental lexicon. No differences were observed in eye movements between Grade 3 groups and between Grade 6 RD group and their RA controls, showing that these groups follow a similar strategy to identify the correctly spelled word. Discussion centers around the role of eye tracking technology in providing valuable information about the mechanisms involved in reading and spelling..